Temporal changes in patient characteristics and outcomes in ST‐segment elevation myocardial infarction 2003–2018. Issue 6 (15th April 2020) - Garcia, Santiago; Schmidt, Christian W.; Garberich, Ross; Henry, Timothy D.; Bradley, Steven M.; Brilakis, Emmanouil S.; Burke, Nickolas; Chavez, Ivan J.; Eckman, Peter; Gössl, Mario; Mooney, Michael R.; Newell, Marc C.; et al.
Abstract: Background: We sought to describe changes in demographic variables, process of care measures, and outcomes of patients treated in a regional ST‐segment elevation myocardial infarction (STEMI) program over the last 15 years. Methods: We describe demographic variables, process of care measures, and outcomes of patients treated in the program in various 5‐year time periods: 2003–2007 ( n  = 1, 821), 2008–2012 ( n  = 1, 968), and 2013–2018 ( n  = 2, 223). The primary outcome measures were in‐hospital and 30‐day mortality. Results: Among 6, 012 STEMI patients treated from 2003 to 2018 we observed a significant increase in mean age at presentation (62 ± 14 to 64 ± 13 years) and diabetes (14–22%, p  < .01). The proportion of patients with cardiogenic shock (CS) and cardiac arrest (CA) pre‐PCI increased significantly from 9.5% to 11.1% and 8.5% to 12.7% ( p  < .05), respectively. The median door‐to‐balloon (D2B) times decreased from 98 to 93 min and total ischemic time decreased from 202 to 185 min (all p  < .05). Despite increased patient complexity, the proportion of nontransfer and transfer patients achieving D2B times consistent with guideline recommendations remained unchanged (for nontransfer patients 79–82%, p  = .45 and for transfer patients 65–64%, p  = .34). Among all STEMI patients, in‐hospital mortality increased during the study period from 4.9 to 6.9% ( p  = .007) but remained stable (<2%) when CA and CS patients were excluded. Conclusions: Over the last 15 years, short‐term STEMI mortality has increased despite improvements in care delivery metrics. Patients with CA and/or CS now represent 10% of STEMI patients and are responsible for 80% of deaths. Therefore, efforts to improve STEMI mortality, and metrics for assessing STEMI programs, should focus on these patients.